2-oxoglutarate-dependent dioxygenases drive expansion of steroidal alkaloid structural diversity in the genus Solanum - Sonawane, Prashant D.; Jozawiak, Adam; Barbole, Ranjit; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Gharat, Sachin A.; Ramot, Ofir; Unger, Tamar; Wizler, Guy; Meir, Sagit; Rogachev, Ilana; et al. (New Phytologist, 2022)
Solanum steroidal glycoalkaloids (SGAs) are renowned defence metabolites exhibiting spectacular structural diversity. Genes and enzymes generating the SGA precursor pathway, SGA scaffold and glycosylated forms have been largely identified. Yet, the majority of downstream metabolic steps creating the vast repertoire of SGAs remain untapped. Here, we discovered that members of the 2-OXOGLUTARATE-DEPENDENT DIOXYGENASE (2-ODD) family play a prominent role in SGA metabolism, carrying out three distinct backbone-modifying oxidative steps in addition to the three formerly reported pathway reactions. The GLYCOALKALOID METABOLISM34 (GAME34) enzyme catalyses the conversion of core SGAs to habrochaitosides in wild tomato S. habrochaites. Cultivated tomato plants overexpressing GAME34 ectopically accumulate habrochaitosides. These habrochaitoside enriched plants extracts potently inhibit Puccinia spp. spore germination, a significant Solanaceae crops fungal pathogen. Another 2-ODD enzyme, GAME33, acts as a desaturase (via hydroxylation and E/F ring rearrangement) forming unique, yet unreported SGAs. Conversion of bitter alpha-tomatine to ripe fruit, nonbitter SGAs (e.g. esculeoside A) requires two hydroxylations; while the known GAME31 2-ODD enzyme catalyses hydroxytomatine formation, we find that GAME40 catalyses the penultimate step in the pathway and generates acetoxy-hydroxytomatine towards esculeosides accumulation. Our results highlight the significant contribution of 2-ODD enzymes to the remarkable structural diversity found in plant steroidal specialized metabolism.
Keywords: Solanum; specialized metabolism; steroidal glycoalkaloids (SGAs); structural diversity; Tomato

BAHD-type acyltransferase concludes the biosynthetic pathway of non-bitter glycoalkaloids in ripe tomato fruit - Sonawane, Prashant D.; Gharat, Sachin A.; Jozwiak, Adam; Barbole, Ranjit; Heinicke, Sarah; Almekias-Siegl, Efrat; Meir, Sagit; Rogachev, Ilana; O'Connor, Sarah E.; Giri, Ashok P.; Aharoni, Asaph (Nature Communications, 2023)
During tomato fruit ripening, bitter and toxic steroidal glycoalkaloids (SGAs) are converted to nonbitter and less toxic forms, but proposed acylating enzyme in pathway remain unknown. Here, authors report BAHD-type acyltransferase that catalyze acylation step in biosynthesis of non-bitter SGAs in tomato. Tomato is the highest value fruit and vegetable crop worldwide, yet produces & alpha;-tomatine, a renowned toxic and bitter-tasting anti-nutritional steroidal glycoalkaloid (SGA) involved in plant defense. A suite of modifications during tomato fruit maturation and ripening converts & alpha;-tomatine to the non-bitter and less toxic Esculeoside A. This important metabolic shift prevents bitterness and toxicity in ripe tomato fruit. While the enzymes catalyzing glycosylation and hydroxylation reactions in the Esculeoside A pathway have been resolved, the proposed acetylating step remains, to date, elusive. Here, we discovered that GAME36 (GLYCOALKALOID METABOLISM36), a BAHD-type acyltransferase catalyzes SGA-acetylation in cultivated and wild tomatoes. This finding completes the elucidation of the core Esculeoside A biosynthetic pathway in ripe tomato, allowing reconstitution of Esculeoside A production in heterologous microbial and plant hosts. The involvement of GAME36 in bitter SGA detoxification pathway points to a key role in the evolution of sweet-tasting tomato as well as in the domestication and breeding of modern cultivated tomato fruit.

Parallel evolution of cannabinoid biosynthesis - Berman, Paula; de Haro, Luis Alejandro; Jozwiak, Adam; Panda, Sayantan; Pinkas, Zoe; Dong, Younghui; Cveticanin, Jelena; Barbole, Ranjit; Livne, Rotem; Scherf, Tali; Shimoni, Eyal; Levin-Zaidman, Smadar; et al. (Nature Plants, 2023)
This study reveals a cannabinoid biosynthetic pathway in Helichrysum umbraculigerum, a plant genetically distant from Cannabis, providing a potential source of new cannabinoids and metabolic engineering tools. Modulation of the endocannabinoid system is projected to have therapeutic potential in almost all human diseases. Accordingly, the high demand for novel cannabinoids stimulates the discovery of untapped sources and efficient manufacturing technologies. Here we explored Helichrysum umbraculigerum, an Asteraceae species unrelated to Cannabis sativa that produces Cannabis-type cannabinoids (for example, 4.3% cannabigerolic acid). In contrast to Cannabis, cannabinoids in H. umbraculigerum accumulate in leaves' glandular trichomes rather than in flowers. The integration of de novo whole-genome sequencing data with unambiguous chemical structure annotation, enzymatic assays and pathway reconstitution in Nicotiana benthamiana and in Saccharomyces cerevisiae has uncovered the molecular and chemical features of this plant. Apart from core biosynthetic enzymes, we reveal tailoring ones producing previously unknown cannabinoid metabolites. Orthology analyses demonstrate that cannabinoid synthesis evolved in parallel in H. umbraculigerum and Cannabis. Our discovery provides a currently unexploited source of cannabinoids and tools for engineering in heterologous hosts.

Steroidal scaffold decorations in Solanum alkaloid biosynthesis - Lucier, Rosalind; Kamileen, Mohamed O.; Nakamura, Yoko; Serediuk, Sofiia; Barbole, Ranjit; Wurlitzer, Jens; Kunert, Maritta; Heinicke, Sarah; O'Connor, Sarah E.; Sonawane, Prashant D. (Molecular Plant, 2024)
Steroidal glycoalkaloids (SGAs) are specialized metabolites produced by hundreds of Solanum species, including important vegetable crops such as tomato, potato, and eggplant. Although it has been known that SGAs play important roles in defense in plants and ``anti-nutritional''effects (e.g., toxicity and bitterness) to humans, many of these molecules have documented anti-cancer, anti-microbial, antiinflammatory, anti-viral, and anti-pyretic activities. Among these, a-solasonine and a-solamargine isolated from black nightshade (Solanum nigrum) are reported to have potent anti-tumor, anti-proliferative, and anti-inflammatory activities. Notably, a-solasonine and a-solamargine, along with the core steroidal aglycone solasodine, are the most widespread SGAs produced among the Solanum plants. However, it is still unknown how plants synthesize these bioactive steroidal molecules. Through comparative metabolomictranscriptome-guided approach, biosynthetic logic, combinatorial expression in Nicotiana benthamiana, and functional recombinant enzyme assays, here we report the discovery of 12 enzymes from S. nigrum that converts the starting cholesterol precursor to solasodine aglycone, and the downstream a-solasonine, a-solamargine, and malonyl-solamargine SGA products. We further identified six enzymes from cultivated eggplant that catalyze the production of a-solasonine, a-solamargine, and malonyl-solamargine SGAs from solasodine aglycone via glycosylation and atypical malonylation decorations. Our work provides the gene tool box and platform for engineering the production of high-value, steroidal bioactive molecules in heterologous hosts using synthetic biology.
Keywords: a-solamargine; Biosynthetic pathway; malonyl-solamargine; Solanum; Specialized metabolites; steroidal glycoalkaloids